2016
DOI: 10.1111/ppa.12532
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Fusarium graminearum and F. meridionale on soybean pod blight and trichothecene accumulation

Abstract: Soybean (Glycine max) is the most important crop in Argentina. At present Fusarium graminearum is recognized as a primary pathogen of soybean in several countries in the Americas, mainly causing seed and root rot and pre‐ and post‐emergence damping off. However, no information about infections at later growth stages of soybean development and pathogenicity of F. graminearum species complex is available. Therefore, the objectives of this study were to compare the pathogenicity of F. graminearum and F. meridiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…These genera have previously been reported as the important pathogens of several soybean diseases, such as seedling blight, root rot and pod and seed decay by Fusarium spp. [ 4 , 10 , 25 , 27 , 37 ]; seedling blight and seed decay caused by Diaporthe/Phomopsis species complex [ 15 , 18 ]; soybean anthracnose caused by Colletotrichum spp. [ 21 , 38 ]; and leaf spot by Alternaria spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These genera have previously been reported as the important pathogens of several soybean diseases, such as seedling blight, root rot and pod and seed decay by Fusarium spp. [ 4 , 10 , 25 , 27 , 37 ]; seedling blight and seed decay caused by Diaporthe/Phomopsis species complex [ 15 , 18 ]; soybean anthracnose caused by Colletotrichum spp. [ 21 , 38 ]; and leaf spot by Alternaria spp.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the frequency of seedborne pathogens among and within seed samples may vary depending on geographical location, host genotype and agricultural practices [ 2 ]. Previous studies showed that only 33% of soybean seeds were infected by Fusarium species in Kansas [ 37 ]. Among nine Fusarium species found in soybean seeds, F. semitectum was the most frequent species in Kansas with the isolation frequency of 56.42% followed by F. proliferatum (19.25%) and F. verticillioides (13.20%), while F. equiseti (2.80%), F. fujikuroi (1.95%) and F. graminearum (0.33%) were isolated in low frequency among naturally infected seeds [ 25 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Members of the Fusarium graminearum species complex (FGSC) can colonize several crops causing diseases such as Fusarium head blight (FHB) in wheat, ear and stalk rot in maize and root rot in soybean (Martinelli et al 2004;McMullen et al 2012;Barros et al 2014;Chiotta et al 2016). Moreover, these species can contaminate grains with type B trichothecenes such as deoxynivalenol (DON), nivalenol (NIV) and its acetylated forms (Desjardins 2006), both associated with feed refusal, vomiting and suppressed immune functions in humans and animals (Pestka 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified species within the FGSC as soybean pathogens in South America showing symptoms of infection such as seed and root rot and pre-and postemergence damping off (Martinelli et al 2004;Pioli et al 2004;Barros et al 2012Barros et al , 2014Chiotta et al 2016). These species persist on residues of host crops such as wheat or maize (Pereyra and Dill-Macky 2008;Guo et al 2010;Chiotta et al 2015a,b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation